Finite element analysis of oil storage tank failure under complex loading conditions - Mashiyane Themba; Tartibu Lagouge; Salifu Smith (MATEC Web of Conferences)
Storage tanks are vital components across industries, especially in the power generation industry, where they are used for oil storage. The internal pressure these tanks are able to withstand greatly affects their longevity and behaviour under service conditions. This paper presents a comprehensive computational study that utilizes Finite Element Analysis (FEA) technique to investigate the failure mechanism of oil storage tanks when subjected to complex loading conditions. In the simulation, FEA software, Abaqus is employed to replicate the operational scenarios which incorporate internal pressure from the stored liquid in the tank, internal pressure developed during discharge and external pressure in the windward direction. Realistic boundary conditions are applied to the tank to accurately mimic real-case scenarios. The stress and strain contour plot shows that the maximum stress (greater than the yield strength of the tank material) and strain with values 485.4 MPa and 2.095 × 10−3, respectively were developed on the surface of the tank in the windward direction. By post- processing, the output database results obtained from the stress and strain analysis in Abaqus using fe-safe, the tank was found to survive 1 429 hours before failure under the specified operating conditions.